Effects of Nrf1 in Hypothalamic Paraventricular Nucleus on Regulating the Blood Pressure During Hypertension - Yu, Xiao-Jing; Xiao, Tong; Liu, Xiao-Jing; Li, Ying; Qi, Jie; Zhang, Nianping; Fu, Li-Yan; Liu, Kai-Li; Li, Yanjun; Kang, Yu-Ming (Frontiers in Neuroscience, 2021)
The incidence rate and mortality of hypertension increase every year. Hypothalamic paraventricular nucleus (PVN) plays a critical role on the pathophysiology of hypertension. It has been demonstrated that the imbalance of neurotransmitters including norepinephrine (NE) glutamate (Glu) and γ-aminobutyric acid (GABA) are closely related to sympathetic overactivity and pathogenesis of hypertension. N-methyl-D-aspartate receptor (NMDAR), consisting of GluN1 and GluN2 subunits, is considered to be a glutamate-gated ion channel, which binds to Glu, and activates neuronal activity. Studies have found that the synthesis of respiratory chain enzyme complex was affected and mitochondrial function was impaired in spontaneously hypertensive rats (SHR), further indicating that mitochondria is associated with hypertension. Nuclear respiratory factor 1 (Nrf1) is a transcription factor that modulates mitochondrial respiratory chain and is related to GluN1, GluN2A and GluN2B promoters. However, the brain mechanisms underlying PVN Nrf1 modulating sympathoexcitation and blood pressure during the development of hypertension remains unclear. In this study, an adeno-associated virus (AAV) vector carrying the shRNA targeting rat Nrf1 gene (shNrf1) was injected into bilateral PVN of male rats underwent two kidneys and one clip to explore the role of Nrf1 in mediating the development of hypertension and sympathoexcitation. Administration of shNrf1 knocked down the expression of Nrf1 and reduced the expression of excitatory neurotransmitters, increased the expression of inhibitory neurotransmitters, and reduced the production of reactive oxygen species (ROS), and attenuated sympathoexcitation and hypertension. The results indicate that knocking down Nrf1 suppresses sympathoexcitation in hypertension by reducing PVN transcription of NMDAR subunits (GluN1, GluN2A and GluN2B), rebalancing PVN excitatory and inhibitory neurotransmitters, inhibiting PVN neuronal activity and oxidative stress, and attenuating sympathetic activity.